THE ACTION OF BENZOL ON CERTAIN CENTRAL NERVOUS REGULATING MECHANISMS - GUERRA PEREZ CARRAL (Rockefeller Foundation, CD MEXICO, DF, MEX, 1947)
Normal cardiovascular roentgen silhouette studied by means of roent-genokymograms of the chests of cadavers after opaque solns had been injected into the large vessels and chambers of the heart Roentgenograms were taken of the chests of cadavers in the
J PHARMACOL EXP THER
Keywords: BENZOYL, NERVOUS, REGULATING, MECHANISMS; CIENCIAS MEDICAS; FARMACODINAMICA; ACCION DE LOS MEDICAMENTOS